Halal risk control at the upstream level of the broiler chicken supply chain - Ramli, Mohd Hasli; Rosman, Arieff Salleh; Khan, Aqeel; Ahmad Fadzillah, Nurrulhidayah; Ghazali, Mohd Al'ikhsan; Samat @ Darawi, Abdul Basit; Saari, Zilal; Jandra, Mifedwil; Omar Jamil, Nor Azwa (Innovare Academics Sciences Pvt. Ltd, 2020)
Halal Assurance System (HAS) was develop over the past 6 years and has undergone several changes and enhancements in terms of its policy requirement in 2019 by JAKIM. However, the implementation of HAS in the poultry industry only discuss the development of this system at the slaughtering stage and also produces downstream of chicken products only. Therefore, there are still no studies that focus on the implementation of HAS at the upstream level of the halal food supply in livestock farms although much research has been conducted. The basic criteria emphasized in the HAS is the determination of the halal control point at each step or process involved. For example, there is five elements in the farming of broiler farms that have been identified as halal risks consisting of food and beverage, medical, farm biosecurity and infrastructure, and logistics were proposed by the authors. Therefore, the qualitative methodology approach through documentation analysis is used to obtain sources of information to discuss the importance of HAS and to explain the elements of halal risk control (HRC) in poultry farming activities. Implementing of this systematic system can also help the industry especially in the livestock sector and the implementation of halal certification policies makes it a key in maintaining the transparency and halal integrity to benefit the consumer starting from the upstream level of halal food supply chain. The study also suggested that the HAS be applied in the poultry sector in future and that it would also have a positive impact if it was implemented in other livestock activities such as others ruminant animals and fish which it is a main supply of halal meat to the Muslim communities in Malaysia.